Pemberian Informasi Pelayanan Maternal di Era Covid-19 Pada Mahasiswa Kebidanan - Harlinah Harlinah; Rizqi Kamalah (Jurnal Empathy Pengabdian Kepada Masyarakat, 2020)
Background: WHO China Country Office on December 31, 2019 reported that there had been pneumonia cases in Wuhan City - China, with global death cases in May 2020 reaching 4.23 million with 290 thousand deaths, 14,729 in Indonesia with 1007 deaths. Seeing that the number of exposure to COVID 19 has increased significantly, the Central Government issued a circular to limit and stop activities that touch the crowds, including teaching and learning activities, whether carried out in the classroom or in the field, this rule can affect students who are preparing their final project reports. The purpose of this community service activity is so that students can find out about the provision of maternal services in the era of COVID-19 and can complete their final project reports. Methods: providing health education online through zoom meetings. Results: The results showed a 100% assement student has been informed of maternal care in the era of Covid-19. Conclusion: The court of the participants numbered 21 people have received information in the Age COVID Maternal care - 19 and documentation of midwifery